PENGARUH PENGUNGKAPAN TANGGUNG JAWAB SOSIAL TERHADAP PROFITABILITAS dan NILAI PERUSAHAAN (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia) - Lestari, Fanny; Nugroho, Paskah Ika (Jurnal Manajemen dan Keuangan, 2010)
Corporate Social Responsibility (CSR) is a concept which the organization, especially the corporation, considers public business with responsible of the influence of their activity towards customers, suppliers, employees, shareholders, publics, and the others stakeholders in the scope of corporation operational aspects. The positive image, which formed as the effect of the implementation of CSR program by a company, brings a good effect towards the success of business activity and company marketing. In a long term, the image will bring a lot of benefits for the company, especially to be a shield in a crisis situation, increase the competitive ability in a middle term and long term, economize the operational cost, and increase the marketing strategy. This research intends to analyze the influence of social responsibility revelation towards the profitability and company value.The data were obtained from 68 anually reports of companies which are listed in ICMD (Indonesia Capital Market Directory) by using purposive sampling method. The analysis technique of this research used simple regression. The data was analyzed by using statistic descriptive analysis, assumption classic test which consisted of normality test and continued with hypothesis test.Statistically, this research shows that the level of the revelation of companiesâ social responsibility, which listed in BEI, are on the average position. It means that some of those companies get a standard score or enough to reveal CSR. The result of this research shows different results for the profitability. The revelation of CSR 07 influences positively towards ROA 07 and 08, while for ratio NPM, both of them are not influenced with the level of the CSR revelation of that company. In addition, the revelation of CSR towards the company value, which measured by using PER ratio, does not have any influences towards PER ratio in the year when CSR was revealed as well as in the following year.Keyword : Corporate Social Responsibility disclosure, ROA, NPM, PER.